Sustentabilidade do patrimônio cultural e as capelas rurais do Triângulo Mineiro e Alto Paranaíba: a Capela da Saudade de Uberlândia (MG) - Côrtes, Aline Soares (2019)
The resources of the planet have been insufficient to sustain the means of production and consumption of contemporary society. This finding has stimulated debate in several areas of knowledge in search of urgent solutions to confront a multifaceted global crisis. However, the predominant research model, based on the mechanistic view, has cluttered the construction and analysis of inter and transdisciplinary relationships capable of reaching a common practical solution. Meanwhile, the perspective of sustainable development had a modest interlocution with the most varied areas, including the conservation of cultural heritage, although these studies generally cover only its environmental aspect. With regard to cultural goods in general, the difficulties faced in their conservation are similar to those imposed on sustainable development, namely: modes of production and consumption, insufficiency of more effective public policies and social exclusion, especially when it comes to interpretation and preservation of cultural goods belonging to the rural environment. The rural area of the Triangulo Mineiro (TM) and Alto Paranaíba (AP) region still preserves a wide range of heritage resources from the 19th and 20th centuries, yet faces preservation difficulties arising from the modification of rural livelihoods after the modernization of the region agricultural system in the 1970s, in which many heritage goods, especially architectural ones, are in a state of neglect and many others have disappeared and could not even be documented. This process of agricultural modernization led to a change in the landscape and rural way of life that hampered the process of safeguarding heritage and endangered socialization practices and various cultural expressions, both material and immaterial. This dissertation aims to reflect on the possible inflections between the conservation of cultural heritage and sustainability in all its spheres and the application of the results in the analysis of a case study: the Chapel of Saudade of Uberlândia (MG). In order to understand the cultural context in which this chapel is inserted, an exploratory inventory of the catholic rural chapels of the whole region encompassed by the Triangulo Mineiro and Alto Paranaíba, in the state of Minas Gerais, was elaborated, seeking to identify this universe and to analyze the challenges and preservation perspectives, prospecting sustainability. The results warn of the need for a paradigm break that can curb the search for unlimited economic growth and generate balance and social equality. Only in this way is it possible to talk about sustainability in the context of the conservation of cultural heritage.